1999
DOI: 10.1159/000040948
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Transiently Appearing Complement-Sensitive Bone Marrow Precursor Cells in Patients with Severe Aplastic Anemia - A Possible Role of High Endogenous IL-2 in Their Suppression

Abstract: In a prospective long-term study on the incidence of paroxysmal nocturnal hemoglobinuria (PNH), 115 consecutive patients with severe aplastic anemia (SAA), 97 treated with antilymphocyte globulin (ALG) and 18 with bone marrow transplantation (BMT), were observed over a period of 4–18 years and tested for the presence of complement-sensitive hematopoietic precursor cells with the bone marrow (BM) sucrose test. Sixteen (14%) of the ALG-treated patients developed clinical signs of PNH between 0.5 and 8 years afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Our previous finding that IL-2 release is low in PNH patients compared to AA patients not developing PNH [25]is in keeping with the role of the immune system in suppressing the PNH clone. The observation that the presence of a GPI-lacking clone before IST does not preclude a response, but that these patients have a high risk of later developing PNH [32]is compatible with our hypothesis: PNH cells present at the time of diagnosis of SAA indicate that the immune system failed to eradicate the abnormal clone, and also allowed its expansion after IST.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Our previous finding that IL-2 release is low in PNH patients compared to AA patients not developing PNH [25]is in keeping with the role of the immune system in suppressing the PNH clone. The observation that the presence of a GPI-lacking clone before IST does not preclude a response, but that these patients have a high risk of later developing PNH [32]is compatible with our hypothesis: PNH cells present at the time of diagnosis of SAA indicate that the immune system failed to eradicate the abnormal clone, and also allowed its expansion after IST.…”
Section: Resultssupporting
confidence: 75%
“…Short-term BM cultures in methylcellulose were performed as described [25]. A human leucocyte-conditioned medium with standard activity was used for stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…GPI-AP-deficient cells are also present in a substantial proportion of patients with AA [5, 6, 7, 8, 9, 10]. Consistent with these findings Bruno Speck’s group demonstrated that the majority of patients with severe AA (SAA) transiently harbour complement-sensitive precursor cells in the bone marrow [11]. …”
Section: Introductionmentioning
confidence: 79%
“…In vivo application of the cytotoxic Campath-1H antibody which is directed against the GPI-AP CD52 led to a reversible emergence of GPI-AP-deficient lymphocytes and monocytes [44, 45]. The association of low endogenous IL-2 release with progression of AA to PNH points at the potential importance of immunological mechanisms for the selection of PNH cells in vivo [11]. …”
Section: Discussionmentioning
confidence: 99%
“…In chimeric knockout mice, PIG-Acells also constitute a minor, static fraction of the marrow or circulating hematopoietic compartments, and PIG-A -and normal cells behave similarly in paired tissue culture assays (12)(13)(14). In most laboratories, PNH patient bone marrow or blood, while often globally deficient in hematopoietic progenitor numbers, has not shown unanticipated outgrowth of either the PIG-A -or normal phenotype cells in colony-forming or long-term culture assays that would indicate a functional difference (15)(16)(17)(18). Only one group has reported a major difference between PIG-A -cells and controls in susceptibility to apoptosis, but this finding has not been reproduced in other laboratories (ref.…”
Section: Models Of Pnh Developmentmentioning
confidence: 99%